Evaluating quantitative pollen representation of vegetation in the tropics: A case study on the Hainan Island, tropical China. (July 2020) - Wan, Qiuchi; Zhang, Yaze; Huang, Kangyou; Sun, Qianwen; Zhang, Xiao; Gaillard, Marie-José; Xu, Qinghai; Li, Furong; Zheng, Zhuo
Highlights: The ERV model can be applied to estimate relative pollen productivity in the tropics. Pollen productivity was estimated for plants with "messy" pollination syndrome. Analysis of vegetation dispersion is useful in the application of the ERV model. The Lagrangian stochastic dispersion model for pollen is not always adequate in the tropics. Abstract: Complex pollen-vegetation relationships in tropical environments have long been a challenge for the interpretation of pollen spectra in terms of vegetation cover. Here, we test the application of the widely-used Extended R -Value (ERV) model in the tropical secondary and planted woodlands of the Hainan Island (China) to estimate relative pollen productivities (RPPs) for common plant taxa occurring as pollen in surface and fossil samples of the region. We collected pollen (soil samples) and related vegetation data within 1500 m radius at 23 random distributed sites within an area of 50 km × 100 km. We found a large difference between the modern pollen assemblages and the related vegetation composition in terms of number and dominance of taxa. We tested the three existing ERV sub-models and three methods to distance-weight vegetation cover, i.e. 1/d, the Prentice's model (using a Gaussian Plume dispersal model, GPM), and the Lagrangian stochastic dispersal model (LSM). The LSM appears to be inappropriate for our dataset. The combination of ERV sub-model 2 and Prentice's model using nine anemophilous and zoophilous (or with "messy" pollination syndrome) taxa was found to provide the best results. The relevant source area of pollen (RSAP) of the soil samples was estimated to ca. 1000–1500 m. The ranking of RPPs is as follows: Castanopsis-Lithocarpus (19.44 ± 0.17) > Asteraceae (8.74 ± 0.05) > Moraceae (6.52 ± 0.08) > Euphorbiaceae (5.22 ± 0.1) > Papilionaceae (2.66 ± 0.05) > Mallotus-Macaranga (2.21 ± 0.08) > Anacardiaceae (1.77 ± 0.04) > Rubiaceae (1.29 ± 0.02) > Poaceae (=1). Violation of the ERV model assumptions of anemophily and stationarity of vegetation composition influenced the performance of the ERV analysis in this study and implied careful evaluation of the results. Nevertheless, the obtained RPPs are considered reliable and will allow to quantify the relative cover of the nine plant taxa in the past. Further studies of this kind will be worthwhile to obtain additional RPP values for a larger number of tropical taxa, even though quantification of past plant cover in the tropics will remain a challenge. The numerous zoophilous taxa may either be absent of the pollen record, or exhibit pollen-vegetation relationships for which the ERV-model is not successful in estimating RPPs. These plant taxa will require other approaches for their quantification in the past.